Novel sources of resistance to Striga hermonthica in Tripsacum dactyloides, a wild relative of maize - Gurney, A L (The New phytologist, 2003)
•  The parasitic weed Striga hermonthica lowers cereal yield in small-holder farms in Africa. Complete resistance in maize to S. hermonthica infection has not been identified. A valuable source of resistance to S. hermonthica may lie in the genetic potential of wild germplasm. •  The susceptibility of a wild relative of maize, Tripsacum dactyloides and a Zea mays-T. dactyloides hybrid to S. hermonthica infection was determined. Striga hermonthica development was arrested after attachment to T. dactyloides. Vascular continuity was established between parasite and host but there was poor primary haustorial tissue differentiation on T. dactyloides compared with Z. mays. Partial resistance was inherited in the hybrid. •  Striga hermonthica attached to Z. mays was manipulated such that different secondary haustoria could attach to different hosts. Secondary haustoria formation was inhibited on T. dactyloides, moreover, subsequent haustoria formation on Z. mays was also impaired. •  Results suggest that T. dactyloides produces a signal that inhibits haustorial development: this signal may be mobile within the parasite haustorial root system